Does Increased Femoral Anteversion Can Cause Hip Abductor Muscle Weakness? - Adnan Apti; Nazif Ekin Akalan (MDPI AG, 2023)
Background: Increased femoral anteversion (IFA) causes functional problems (i.e., tripping, frequently falling, and fatigue) by affecting the pelvis and lower extremity biomechanics. In the frontal plane, increased contralateral pelvic drop and ipsilateral hip adduction, which are mainly considered deteriorated hip abductor muscle mechanisms, are associated with hip and knee injuries. Aims: The aim of this study was to examine the effects of femoral anteversion on hip abductor weakness and frontal plane pelvis-hip biomechanics during walking. Methods: The study included nine subjects with increased femoral anteversion and a control group of eleven subjects. Maximum isometric voluntary contraction (MIVC) values of the hip abductor muscles were measured with a handheld dynamometer. Three-dimensional gait analysis was performed for kinetic, kinematic, and temporo-spatial gait parameters. Non-parametric tests were used for statistical analysis (p < 0.05). Results: There was no significant difference found between the MIVC values of the IFA and control groups (p = 0.14). Moreover, no significant difference was determined between the ipsilateral peak hip adduction (p = 0.088) and contralateral pelvic drop (p = 0.149) in the stance phase. Additionally, there was no correlation between the peak hip adduction angle in the stance phase and normalized MIVC values in the IFA group (r = −0.198, p = 0.44), or in the control group (r = −0.174, p = 0.55). The deviations of pelvic rotation (p = 0.022), hip internal rotation (p = 0.003), and internal foot progression (p = 0.022), were found to be higher in the IFA group than in the controls. Conclusions: IFA may not be associated with hip abductor muscle weakness, and it may not lead to the hip adduction and pelvic depression that can be seen in hip abductor weakness. Increased pelvic rotation and internal hip rotation during walking might be considered as a compensation for the femoral head-acetabulum alignment mechanism in the frontal plane.